Dietary fat intake and prevention of cardiovascular disease: systematic review. Issue 7289 (31st March 2001) - Hooper, Lee; Summerbell, Carolyn D; Higgins, Julian P T; Thompson, Rachel L; Capps, Nigel E; Smith, George Davey; Riemersma, Rudolph A; Ebrahim, Shah
Abstract: Objective: To assess the effect of reduction or modification of dietary fat intake on total and cardiovascular mortality and cardiovascular morbidity. Design: Systematic review. Data sources: Cochrane Library, Medline, Embase, CAB abstracts, SIGLE, CVRCT registry, and biographies were searched; trials known to experts were included. Included studies: Randomised controlled trials stating intention to reduce or modify fat or cholesterol intake in healthy adult participants over at least six months. Inclusion decisions, validity, and data extraction were duplicated. Meta-analysis (random effects methodology), meta-regression, and funnel plots were performed. Results: 27 studies (30 902 person years of observation) were included. Alteration of dietary fat intake had small effects on total mortality (rate ratio 0.98; 95% confidence interval 0.86 to 1.12). Cardiovascular mortality was reduced by 9% (0.91; 0.77 to 1.07) and cardiovascular events by 16% (0.84; 0.72 to 0.99), which was attenuated (0.86; 0.72 to 1.03) in a sensitivity analysis that excluded a trial using oily fish. Trials with at least two years' follow up provided stronger evidence of protection from cardiovascular events (0.76; 0.65 to 0.90). Conclusions: There is a small but potentially important reduction in cardiovascular risk with reduction or modification of dietary fat intake, seen particularly in trials of longer duration.